Soft Skills in the Development of Team-Based Electronic Learning Portfolio - Zainal Abidin, Azizan (2010)
The top qualities of an effective engineer include not only technical competence but also soft skills which may be hard to acquire while already on the job. Fulfilling stakeholders’ demand, educators design the curriculum for engineering programs with the objectives of producing graduates capable in not only technical competence but also possess the equally important soft skills. This calls for a good variety of assessment techniques of student learning in order to ensure a more comprehensive measurement of performance. With the limitations of the traditional pen and paper assessment approach, the electronic learning portfolio is one alternative that is integrated in the assessment of Differential Equations course in the Universiti Teknologi PETRONAS, Malaysia. Two hundred and forty two engineering undergraduates are involved in the study and are randomly grouped into fifty one teams to develop team-based electronic Differential Equations Learning Portfolio, acronym e-DELP. In the process of developing the portfolio electronically, each team strategize collectively in conformance to the criteria explicitly transcribed on the course e-learning portal. Objectively, e-DELP development creates a platform that provides participants with the opportunity to exercise their soft skills while exploring the applications of Differential Equations in the real world problems and new skills in using Equation Editor and Power Point Presentation Skills. The participants’ major task is to design a learning portfolio, team-based and problem-based within 7 weeks of a fourteen-week semester. The deliverable is a four-component learning portfolio, comprising members’ demographic details, solutions to five modelling problems involving Ordinary Differential Equations, their evaluation of the course and delivery, and reflections of their learning experience; electronic-based and saved on a compact disc. A questionnaire is employed to measure the general attitude towards the integration of e-DELP, and individual interview sessions are conducted to further confirm the data obtained. The objective of this paper is to present some qualitative findings of the soft skills that participants acquire through the process of working on e-DELP, retrieved from the verbatim written comments in their evaluation and reflections, verbal and non-verbal feedback during the interviews. The results indicate that there is more to the learning than just skills in solving Ordinary Differential Equations which are of great value in the preparation of the future well-rounded engineers.